Eradicating of Cu2+ and Fe2+ ions in single and binary system using microcrystalline cellulose extracted from gossypium hirsurtum plant / Mohammad Abdullah ... [et al.] - Abdullah, Mohammad; Rahmat, Nur Nazifa; Zainal, Muhammad Afiq; Zul' idham, Mohamad Aiman Hakim
In this vast developing world, the presence of heavy metals in water such as river, ocean and lake which were discharged by industrial work arise severe environmental problem especially to human health, water ecosystem and fauna biology. Heavy metals such as copper, iron and others are very dangerous if exposed to the living things thus drinking or inhaling them could brought to very serious acute diseases. Nowadays, most of the wastewater treatment are less effective in treating this contaminant. In this case, to improve the efficiency of water treatment plant, the adsorbent polymer is used to remove copper (Il) and iron (Il) as heavy metals. The adsorbent used is microcrystalline cellulose which were analysed to get the results on removing both the heavy metals in binary system. The efficiency of the adsorption of microcrystalline cellulose was then assessed on Field Transform Scanning Microscopy (FESEM) to determine the structured morphology due to the adsorption effect. The last result measure the percentage of removal of the adsorbent by using Inductively Coupled Plasma (ICP) as the microcrystalline cellulose is very efficient absorbent in removing copper (II) and iron (II) from aqueous solution. The analysis on Fourier Transform-Infra Red (FT-IR) were assessed to determine the molecular bonding and functional groups in cellulose materials since the cellulose molecules contained different vibration frequencies. The presence of the functional groups in cellulose samples will be record on FTIR. As the adsorption of copper (II) and iron (II) ions into adsorbent is affected by the amount of dosage, the objective is achieved. Thus, the use of microcrystalline cellulose shows a good potential as a adsorbent for removing copper (II) and iron (II).